Population Stratification in Genetic Association Studies. (13th February 2018) - Hellwege, Jacklyn N.; Keaton, Jacob M.; Giri, Ayush; Gao, Xiaoyi; Velez Edwards, Digna R.; Edwards, Todd L.
Abstract: Population stratification (PS) is a primary consideration in studies of genetic determinants of human traits. Failure to control for PS may lead to confounding, causing a study to fail for lack of significant results, or resources to be wasted following false‐positive signals. Here, historical and current approaches for addressing PS when performing genetic association studies in human populations are reviewed. Methods for detecting the presence of PS, including global and local ancestry methods, are described. Also described are approaches for accounting for PS when calculating association statistics, such that measures of association are not confounded. Many traits are being examined for the first time in minority populations, which may inherently feature PS. © 2017 by John Wiley & Sons, Inc.